The wine list design of upscale restaurants - Brochado, A.; Vinhas da Silva, Rui (International Journal of Humanities and Social Sciences, 2014)
This paper investigates the structure and content of the wine lists in upscale restaurants in Portugal (N=61). The respondents considered that a wine list should be easy to use and to modify, welldesigned, modern and varied. Respondents also stated that they perform on average 6 revisions to the wine list per year. The restaurant owner, the restaurant manager and the sommelier were the main persons in charge of the wine list design. One of the most important reasons for selecting wines across most restaurants was to ‘complement the menu’ and ‘pairing food with wine’. Restaurants also reported to be relatively independent from suppliers and magazine evaluations. Moreover, this work revealed that the restaurant wine list is considered by restaurateurs as a strategic tool to sell wine as a complement to the menu, to improve customer satisfaction and loyalty, to increase restaurant value and to enhance a successful positioning.